Does the format matter? How the multiple-choice format might complicate the MKT items - Fauskanger, Janne; Mosvold, Reidar; Bjuland, Raymond; Jakobsen, Arne (NOMAD Nordic Studies in Mathematics Education, 2011)
In order to design appropriate professional development programs for teachers, an instrument has been developed in the U.S. to measure teachers’ mathematical knowledge for teaching. The process of translating and adapting these measures for use in other countries involves several challenges. This article focuses on issues related to the multiple-choice format of the items. Analyses of focus-group interviews reveal that the multiple-choice format may complicate the items. The teachers’ reflections about the format in this Norwegian case contribute to the understanding of this important challenge.